MEDICO-SOCIAL ASPECTS OF THE EPIDEMIOLOGY OF TUBERCULOSIS IN MODERN CONDITIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Tuberculosis (TB) remains one of the most significant public health challenges globally, affecting millions of people each year. Despite significant advancements in medical science and public health, TB continues to pose a threat, particularly in low- and middle-income countries. The complex interplay of medical and social factors in the epidemiology of TB necessitates a comprehensive understanding of the medico-social aspects surrounding the disease in modern conditions. This article aims to explore the various medico-social factors that influence the epidemiology of tuberculosis, highlighting their significance in the context of contemporary healthcare systems.